(1155) some aspects of the employment problem in the Arab republic of Egypt بعض جوانب مشكلة البطالة في جمهورية مصر العربية - mongi, mohammed A.; hanafi, mohammed N. (the institute of national planning, 2018)
the problem of increasing labour absorptive capacity is not merely how to absorb the redundant labour but rather how to make the best use of the available resources, including labour. however, the whole process of employment creation may be considered as containing a great number of different variables which can be distinguished from each other for analytical purposes.